A prospective study on clinical profile and incidence of acute kidney injury due to hair dye poisoning - Ramulu, P.; Rao, P. Amruth; K., Kanthi Swaroop; K., Paul Marx; Devi, Ch. Venkata Ramana (International Journal of Research in Medical Sciences, 2016)
Background: Globally suicides are mounting at an alarming rate over the last few decades thus claiming the most productive age group of the society. Developing country like India is no exception to this needless increasing toll. Methods: This study was a prospective observational study with 31 patients recruited at Osmania General Hospital between November 2011 – October 2013. Patients of alleged hair dye ingestion admitted in MICU were taken up for study after the exclusion criteria were ruled out. Informed consent was obtained from every patient or patient’s relatives. All routine laboratory investigations were done basing on standard clinical procedures and protocols and patient related clinical information were recorded on the prepared proforma from the time of hospital admission till discharge or death. The presence of AKI was defined and graded as per the RIFLE criteria. Results: The present work examines 31 cases of suicidal ingestion of hair dye, out of which males were 6 (19.35%) and females were 25 (80.64%). It was observed that the tendency to commit suicide was more in the age group 21 -30 years with males (30%) and females (70%). 19% of total patients who ingested more than 50 ml of dye had developed Acute Kidney injury requiring hemodialysis. Upon treatment about 58% of patients were discharged from hospital in good general health condition, Four patients expired due to respiratory complications with pneumonia, ARDS, sepsis and ARF. Conclusions: So in current scenario of emerging hair dye poisoning, it is imperative for a timely intervention by reducing the time of admission in hospital and also early management by clinicians is the need of an hour.